A critical appraissal of the home-based food security projects with reference to layers at Makhuduthamaga Sekhukhune District in Limpopo Province - Monyela, Mante Thabitha Daisy (My University, 2007)
It is beyond doubt that a large proportion of the population in the rural areas are experiencing great difficulty in securing adequate food in both amount and quality. Poverty alleviation programs are embarked in various countries with Makhuduthamaga being no exception. The study was designed to evaluate the home-based egg production projects. The study was conducted at Makhuduthamaga sub- District of Sekhukhune District of Limpopo province. Two instruments were used for data collection namely Delphi technique and two structured questionnaires. The Delphi technique was used for both the beneficiaries and the extension officers to identify, list and rank in order of importance the constraints which impacted negatively on egg production as well as the actions taken to address those constraints. Two separate questionnaires were also used to collect data from both the beneficiaries and the extension officers. Out of twenty villages a list of 231 beneficiaries of starter up packs was identified. Krecjcie and Morgan (1970) sample estimation required 144 randomly selected beneficiaries of starter up packs to participate in the study which reflected 0.6 margin of error. The two questionnaires with open ended and closed ended questions were piloted at Fetakgomo District in four villages with thirty one beneficiaries and ten extension officers. Reliability was found to be 0.81 skills, 0.80 for support from extension officers and 0.61 for government expectations. The Statistical Package for the Social Sciences was used for the entering data collected. Descriptive statistics were used to analyse data. The findings revealed that the majority of the beneficiaries fall within the prescribed selection criteria. Almost all except one village were given the starter up packs namely 18 layers, four bags of laying mash, cage, nipples, feeding trays and a cage as outlined in the policy. Training was considered by both the beneficiaries and the extension officers as inadequate for effective and efficient running of the home based egg production projects. The results revealed that the majority of beneficiaries did not meet government expectations. An acknowledgement was made that during the implementation of projects mistakes were committed by both beneficiaries and extension officers. Analysis of variance was also used to determine the relationship between the level of education and the extent to which government expectations were met. There was no significant relationship between skills such as technical, management, financial, administration and the extent to which government expectations were met. However there was a significant relation between marketing skills and levels of education. The majority of beneficiaries had a low level of education. Pearson correlation coefficient was used to determine whether there is a relationship between skills and support from the extension officers and the extent to which government expectation were met. Skills such as technical and marketing as well as the support from the extension officers attributed much to variations with regard to the extent to which government expectation were met. Constraints were also encountered which impacted negatively on egg production. Extension officers identified the following constraints such as survey not done prior to distribution, insufficient human resources, training, insufficient monitoring, inadequate transport, inability of beneficiaries to purchase feed, inadequate starter packs and failure to establish cooperatives. Beneficiaries identified constraints such as feed, training, diseases and unavailability of veterinarian, mortality of layers on arrival, theft and predation, inadequate starter packs, layers not of the same age and cages that are too small. Out the constraints mentioned only three namely insufficient transport, inadequate starter up packs `and one aspect on feed i.e. soft shelled eggs were addressed. Although the majority of beneficiaries considered home based egg production projects inadequate in providing access to adequate food, slightly over half of them favoured them as future household projects.
Thesis (M.Sc) (Agriculture) --University of Limpopo, 2007.
Keywords: egg-production projects; Limpopo Province; home-based food security projects